The Influence of Dividend Policy, Investment Policy, and Profitability on Firm Value - Arifathul Khoiriyah; Dista Amalia Arifah; Maya Indriastuti; Winarsih (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to analyze the effect of Dividend Policy, Investment Policy, and Profitability on Firm Value. Firm value reflects investor perceptions of the company’s performance and prospects, which are also related to stock prices, where the higher the firm value, the greater the prosperity of its owners. The population of this study is the Manufacturing Companies in the primary consumer goods sector listed on the IDX in 2021-2023. The sampling technique in this study used purposive sampling, with a sample of 42 companies. The results of the study show that Dividend Policy does not affect firm value, while investment policy and profitability have a positive and significant effect on firm value.